Mindful unlearning in unprecedented times: Implications for management and organizations. Issue 5 (November 2022) - Vu, Mai Chi; Nguyen, Loi A
Crises trigger both learning and unlearning at both intra-organizational and inter-organizational levels. This article stresses the need to facilitate unlearning for effective crisis management and shows how we could use mindfulness practice to enhance unlearning and transformative learning in a crisis. This study proposes the conceptualization of mindful unlearning in crisis with different mechanisms to foster unlearning in three stages of crisis (pre-crisis, during-crisis, and post-crisis). These mechanisms include mindful awareness of impermanence and sensual processing (pre-crisis stage), mindful awareness of interdependence and right intention (crisis management stage), and mindful awareness of transiency and past experiences (post-crisis stage).